Pemikiran Imam Al-Nawawi Mengenai Etika Pendidik dalam Kitab At-Tibyan Fii Adabi Hamalatil Al-Qur’an : Imam Al-Nawawi's Thoughts on Educator Ethics in the Book of At-Tibyan Fii Adabi Hamalatil Al-Qur'an - Muhammad Nurudin (ISEDU : Islamic Education Journal, 2024)
One of the most important factors in achieving educational achievement during the learning process is educational ethics. Being a guide for children is an educational responsibility. In other words, every action taken towards education, be it in life, speech or action, has a great impact on the lives of the students they develop as individuals. Educational ethics develops in a variety of references from classical and modern books and works. In this case, in-Tibyan Fi Adab Hamalatil Al-Qur'an is a book that must be observed. In-Tibyan Fi Adab Hamalatil Al-Qur'an, Imam Al-Nawawi's views on the ethics of education are up for debate in this study. Literature research methods are used in quantitative research description of this study, and content analysis is used to analyze the data. The results of the study stated that 15 major ethical principles can be used to explain the views of Imam Al-Nawawi on the ethics of education in the Qur'an in-Tibyan Fii Adabi Hamalatil.